Nexus between Level and Factors of Job Satisfaction in Nurses of Multan City (Pakistan): A Study of Public Hospitals - Afzal, Saima; Sidra Hussain; Adeela Manzoor (Journal of Peace, Development and Communication, 2021)
The present study was intended to determine the level and factors of nurse’s job satisfaction working at public hospitals of Multan city, Pakistan. A cross-sectional survey was employed to collect data (March, 2019-May, 2019) from 441 nurses by utilizing a disproportionate sampling technique. Data collection was done by the application of a self-administered questionnaire e.g. McCloskey/ Mueller Satisfaction Scale. (MMSS).The level of J.S was measured by correlation analysis and to determine the most prevalent factor of J.S regression analysis was done. Correlation coefficient value of socio-demographic variables described that cadre, shiftwork, work experience, marital status, no of children, and working hours demonstrated a significant relationship with J.S. However, regression analysis of MMSS demonstrated a strong positive association with J.S. Nurse’s satisfaction could be improved through cultivating a positive work environment, increase in remuneration, decrease in workload, and maintaining work/family balance.